Structure reactivity relationship in the accelerated formation of 2, 3-diarylquinoxalines in the microdroplets of a nebuliser. Issue 6 (December 2019) - Hayat, Nadia; Fenwick, Nathan W; Saidykhan, Amie; Telford, Richard; Martin, William HC; Gallagher, Richard T; Bowen, Richard D
Competition experiments in which 1, 2-phenylenediamine, C6 H4 (NH2 )2, condenses with equimolar quantities of benzil, (C6 H5 CO)2, and a 3, 3′- or 4, 4′-disubstituted benzil (XC6 H4 CO)2 (X = F, Cl, Br, CH3 or CH3 O) to form a mixture of 2, 3-diphenylquinoxaline and the corresponding 2, 3-diarylquinoxaline (Ar = XC6 H4 ) in the microdroplets produced in a nebuliser allow a Hammett relationship with a ρ value of 1.85 to be developed for this accelerated condensation in the nebuliser. This structure reactivity relationship reveals that an appreciable amount of negative charge builds up on the carbon of the carbonyl group of the benzil during the rate-limiting step of the reaction, thus confirming that this process involves nucleophilic addition of the 1, 2-phenylenediamine to the benzil. In general, the presence of an electron donating substituent, particularly in the 4 and 4′ positions, in the benzil retards the reaction, whereas an electron attracting substituent, especially in the 3 and 3′ position, accelerates it.